Penerapan Metode Ceramah Menggunakan Aplikasi Scocrative dalam Meningkatkan Pemahaman PAI Kelas VIII di SMP Tunas Utama - Aditya Ramadhan; Adiyas Adiyas; Arum Anastasya; Dewi Nurhaliza; Dila Rahma Pebriana; Khalid Ramdhani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this observation was to determine how effective teaching with the lecture method combined with the Socrative application is in improving the understanding of the Islamic Religious Education (PAI) curriculum among grade VIII students of SMP Tunas Utama. One of the main results of this study is the active involvement of students and the application of technology in the PAI learning process. Planning, implementation, observation, and reflection are two main elements of the applied methodology, known as classroom action learning (CAR). The tools used include observation sheets, comprehension tests, and questionnaires for student responses. The results of the study showed that the application of the Socrative method was able to improve interaction between students, learning motivation, and understanding of religious concepts. This increase can be seen from the increase in average scores and learning completeness from the first period to the second period. In this way, the combination of the flipped learning method with interactive technology such as Socrative has succeeded in improving the quality of learning in the PAI subject.